Journal of chemical education
Features the online edition of the "Journal of Chemical Education" (JCE), published monthly in Madison, Wisconsin, by the Division of Chemical Education, Inc. of the American Chemical Society (ACS). "JCE" publishes articles of interest to those who teach chemistry at all levels, from high school through graduate courses. Posts a publication overview, a toll-free order number, author guidelines, and subscription information. Links to current and past issues of the "Journal," chemistry-related Internet resources, and "JCE" software.